Early Grief and Coping with Stress in the Informal Caregiver of the Elderly - Aponte-Daza, Vaneska Cindy (2022)
Background: Anticipatory grief is the process that some people go through before the death of a loved one or their death is confirmed. It occurs when several circumstances lead to the expectation that sooner or later a loved one, such as a relative, a partner or a friend, is going to die. Objective: The objective of the study was to find out what are the stress coping strategies and the personal care and caregiver factors that benefit, or put at risk, grieving in informal caregivers of the elderly. Method: 272 informal caregivers participated. The Caregiver Grief Scale by Meichsner et al. (2016) and the Brief Coping Scale to Stress (COPE 28) by Carver (1997) were used. Results: The results show that anticipatory grief is influenced by coping: emotional pain due to coping based on support (OR = .236) and on avoidance of emotion (OR = 3.751), and being in care all day (OR = 3.061). Emotional loss is estimated by problem-focused coping (OR = .201), when the caregiver is an older adult (OR = .303), and by part-time caregiving (OR = 2.029). Acceptance of loss is influenced by problem-focused coping (OR = .172), emotion-avoidance coping (OR = 4.409), being a young adult caregiver (OR=2.361), and by care for almost the entire day (OR = .536). In addition, absolute loss was associated with problem-focused coping (r = .249) and substance-avoidance coping (r = .216). Conclusions: This study manages to identify personal factors and types of coping with stress that favor, or reduce, anticipatory grief in informal primary caregivers. In particular, the probability of presenting emotional pain increases according to coping based on support or spiritual, but decreases with coping based on emotional avoidance and greater coexistence with the patient. Authorship contribution VCAD: literature review, elaboration of the introduction, justification, problem statement, theoretical framework, population selection, test taking, and elaboration of results and conclusions. FPV: data collection, data base elaboration, data analysis, creation of tables, elaboration of the method, elaboration of results and conclusions. BPT: teacher guide. FG: revision of the article and suggestions for corrections.